Concentração de resveratrol e expressão de resveratrol sintase em espécies de Arichis - Carvalho, Paula Andréa Sampaio de Vasconcelos [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Resveratrol is a phytoalexin produced under biotic and abiotic stresses. It has been found in a restricted number of plant species including peanut (Arachis hypogaea) and its wild relatives. This phytochemical has antioxidant properties, being considered a promising antitumour, cardioprotective and neuroprotective agent. Peanut is an allotetraploid specie with an AABB genomic constitution. Arachis ipaënsis and A. duranensis are the donors of the B genome and the A genome, respectively. Previous studies have shown that wild species of the genus Arachis can produce resveratrol. Therefore, the evaluation of other species of thus genus and the analysis of the variation in the production of resveratrol between accessions is essential for better exploitation of wild species in the genus Arachis. It also important the understanding of the variation in resveratrol concentration between species and accessions and that could be reached through the better understating of the role resveratrol synthase.. . The aims of this work were to evaluate the variation in resveratrol production between species (A. hypogaea, A. stenosperma, A. valida, A. wiliamsii, A. duranensis, A. ipaënsis and in a synthetic amphidiploid derived from these two wild species A. duranensis and A. ipaënsis) and between accessions of the same specie (A. hypogaea and A. stenosperma) through HPLC, and to quantify the expression of resveratrol synthase by RT-qPCR in A. hypogaea, A. duranensis, A. ipaënsis and in a synthetic amphidiploid. Leaves for the test and control groups were collected from plants cultivated in a greenhouse and three biological replicates were evaluated for each specie. The synthesis of resveratrol in leaves was induced by treatment with UV for 2 hours and thirty minutes and then the difference in the concentration of resveratrol between species and between the accessions and cultivars of the same species was analyzed. We found new ...

O resveratrol é uma fitoalexina produzida em função de estresses bióticos e abióticos e foi encontrado em um número limitado de espécies de plantas, incluindo o amendoim (Arachis hypogaea) e seus parentes silvestres. Este tem também propriedades antioxidantes e em função disso é um promissor antitumoral, cardioprotetor e neuroprotetor. O amendoim é um alotetraploide de constituição genômica AB sendo A. ipaënsis e A. duranensis os doadores de seus genomas B e A, respectivamente. Estudos prévios demonstraram que algumas espécies silvestres do gênero Arachis produzem resveratrol e que ampla variabilidade genética para diferentes características existe entre acessos das espécies silvestres, incluindo ampla variação nos níveis de resistência a doenças fúngicas e nematoides. Portanto, a avaliação de um maior número do gênero e a investigação da variação da produção de resveratrol também entre acessos é fundamental para uma exploração mais adequada das espécies silvestres do gênero Arachis. O melhor entendimento das causas da variação na produção de resveratrol sem dúvida contribuirá para o uso das mesmas e o primeiro passo para esse entendimento sem duvida passa pela identificação do padrão de expressão da resveratrol sintase (RS). Este trabalho tem como objetivos avaliar a variação na produção de resveratrol entre espécies (A. hypogaea, A. stenosperma, A. valida, A. wiliamsii, A. duranensis, A. ipaënsis e um anfidiploide sintético proveniente do cruzamento artificial entre A. duranensis e A. ipaënsis) e entre acessos de duas espécies(A. hypogaea e A. stenosperma) por meio de HPLC e avaliar a expressão relativa da resveratrol sintase por meio de RT-qPCR em A. hypogaea, A. duranensis, A. ipaënsis e um anfidiploide sintético. Folhas foram coletadas de plantas cultivadas em casa de vegetação para os grupos teste e controle e três repetições biológicas ...
Keywords: Leguminosa; Fitoalexina; Botânica - Classificação; Plantas - Resistencia; Variação (Biologia); Plants; Variation (Biology)